Catalysts in the water-gas shift reaction: A comparative review of industrial and academic contributions - Roshni Patel; Prashandan Varatharajan; Qi Zhang; Ze Li; Sai Gu (Carbon Capture Science & Technology)
Rising energy demand leads to a heavy dependence on fossil fuels and contributes significantly to increasing greenhouse gas emissions. Consequently, alternative solutions to mitigate these pollutants are continually being developed, necessitating a transition to renewable and cleaner energy sources. Hydrogen production via the water-gas shift (WGS) reaction, where CO and water react over a suitable catalyst is an approach. Cu-Zn and Fe-Cr catalysts are used in industry for this reaction at low temperatures (LT) and high temperatures (HT), respectively. Research into applying the WGS reaction in portable devices emphasizes developing catalysts to enhance hydrogen production and overcome the limitations of industrial catalysts, given the reaction's complex mechanism and kinetics. Research on the redox and associative pathways is extensive, and studies on carboxyl and formate mechanisms are ongoing. The intricacy of these mechanisms and kinetics facilitates additional research into reactor design to support process applications, including ammonia and Fischer-Tropsch (FT) synthesis. Numerous commercial catalyst accomplishments are recognized in this review, including the chromium-free HT zinc and the sulphur-tolerant cobalt-molybdenum catalysts. Additionally, research has been done on conventional Cu-Zn and Fe-Cr catalysts in the lab to overcome issues like sintering and chromium toxicity, respectively. Various strategies are examined, including nickel and noble metals catalysts. The formulation and preparation techniques, loading volumes, support modifications, promoter additions, and shape were all examined to observe impacts on CO conversion and hydrogen production.